УКРАЇНСЬКИЙ І РУМУНСЬКІЙ ПОЛІМЕТРИЧНИЙ ВІРШ У ТВОРАХ ПОЕТЇВ-РОМАНТИКІВ - Paladian, Kristiniia (Casa Cärpi de Stiintä, 2016)
The article concerns investigation of Ukrainian and Romanian poetry in terms of use polymetric compositions. This approach nables a deeper and thinner reveal the specifics - the similarities and differences - both in the poetry of neighboring peoples and adds a lot to the understanding of the evolution o f European diversification in general During the Romanticism there is a ignificant enrichment of metric organization works. Romantic poets produce new types of poems, new means of poetical construction. Internal modifications of poetic forms, deviation from the basic size, mix of classical and non-classical poem or verse to prose are fixed in their poems. This architectonic poetry produces new types of rhythmic expression, which we assign to polymetric designs. Polymetric design fix in both literatures: the Romanian prevalent form within two syllables sizes, in Ukrainian - forms within two and three syllables sizes. In Romanian poetry also present examples of polimetria within one meter polyrhythmic composition). The dominant form, both in Ukrainian and in Romanian poetry stands romantic type of PC that is characterized by the absence of a dominant size. This multisegment composition consisting of different meter size thematically and compositionally equal parts that are haphazardly interspersed in the text. These forms are in Ukrainian literature: T. Shevchenko, A. Metlynsky, M. Kostomarov, P. Kulish; in Romanian: M. Eminesku, V Aleksandri, D. Bolintinyanu, B. P. Hashdeu. In general, both Ukrainian and Romanian poetry, with a help of metric enrichment through metric verse forms, represents great opportunities in developing polymetric verse.
Ukrainian and Romanian Polymetric Verse in the Works of the Romantic Poets
Keywords: versification; meter; size; polyrhythmic composition; polymorphic strukture